Effect of Black Pepper Extract (Piper nigrum L) towards Streptococcus Mutans Growth: Pengaruh Ekstrak Lada Hitam (Piper nigrum L) terhadap Pertumbuhan Streptococcus Mutans - Hakim, Rachmi Fanani; Fakhrurrazi; Alwi, Fadli (TALENTA, 2020)
Streptococcus mutans is a Gram-positive facultative anaerobic bacteria which has become the main cause of dental caries. Black pepper (Piper nigrum L ) is one of herbal plants that compose antibacterial compounds including alkaloids, flavonoids, tannins, and essential oils. This study aims to determine the effect of black pepper (Piper nigrum L.) extract to inhibit of Streptococcus mutansgrowth. Black pepper extracts ware made by using maceration method. The effect of black pepper extract ( Piper nigrum L. ) in inhibition of Streptococcus mutansgrowth by using the disc diffusion method on Mueller Hinton Agar media. The concentration of black pepper ( Piper nigrum L.) extracts used in this study were 6.25%, 12.5%, 25%, 50%, 75%. The results of this study were analyzed by using the one-way ANOVA test showed that there was significant effect of black pepper extract on Streptococcus mutans growth with p-value (p <0.05), and then the data was tested by Least Significant Difference (LSD). Conclusion of this study showed that there was an effect of black pepper ( Piper nigrum L.) extract in inhibition of Streptococcus mutans growth with concentrations 75% is the optimum concentration which value 16.8 mm.